Religious voices in self-narratives : making sense of life in times of transition - Zock, Hetty; Buitelaar, Marjo (Religion and society (Hague, Netherlands), 2013)
In present-day pluralistic and individualized societies, the question of how individuals appropriate religious traditions has become particularly relevant. In this volume, psychologists, anthropologists, and historians examine the presence of religious voices in narrative constructions of the self. The focus is on the multiple ways religious stories and practices feature in self-narratives about major life transitions. The contributions explore the ways in which such voices inform the accommodation and interpretation of these transitions.